Differentiated adipose‐derived stem cells promote peripheral nerve regeneration. Issue 1 (18th April 2020) - Yamamoto, Daiki; Tada, Kaoru; Suganuma, Seigo; Hayashi, Katsuhiro; Nakajima, Tadahiro; Nakada, Mika; Matsuta, Masashi; Tsuchiya, Hiroyuki
Abstract: Introduction: Many reports have indicated that adipose‐derived stem cells (ADSCs) are effective for nerve regeneration. We investigated nerve regeneration by combining a polyglycolic acid collagen (PGA‐c) tube, which is approved for clinical use, and Schwann cell‐like differentiated ADSCs (dADSCs). Methods: Fifteen‐millimeter‐long gaps in the sciatic nerve of rats were bridged in each group using tubes (group I), with tubes injected with dADSCs (group II), or by resected nerve (group III). Results: Axonal outgrowth was greater in group II than in group I. Tibialis anterior muscle weight revealed recovery only in group III. Latency in nerve conduction studies was equivalent in group II and III, but action potential was lower in group II. Transplanted dADSCs maintained Schwann cell marker expression. ATF3 expression level in the dorsal root ganglia was equivalent in groups II and III. Discussion: dADSCs maintained their differentiated state in the tubes and are believed to have contributed to nerve regeneration.